TINJAUAN YURIDIS PERIZINAN PENDIRIAN DAN OPERASIONAL RUMAH SAKIT DI KABUPATEN PURBALINGGA PROVINSI JAWA TENGAH - , Cecep Triwibowo ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aimed to 1) Determine the implementation of the hospital establishment and operational in Purbalingga with sub-goal as a) determining the process of hospital establishment and operational, b) determining the level of compliance of the hospital toward the licensing requirement, c) finding out supervision and guidance on the establishment and implementation of hospital operations. 2) Determining the constraints in the license in Purbalingga. 3) Determining the efforts to facing the constraints in the implementation of hospital establishment in Purbalingga. This study used a qualitative descriptive, empirical juridical approach. Juridical empirical was intended to examine the effectiveness of the operation of law in society. The study was conducted using interviews supported the theory and study the document, then narrated in the form of descriptive. The results of this study were 1) implementation of the licensing process in Purbalingga involving relevant agencies of Department of Health, Office of Integrated Licensing Services, and Environment Office. Permits issued by the hospital on the recommendation of the Regent District Health Office. 2) Compliance hospitals in implementing the hospital licensing process were low. Licensing requirements was mandated in Regulation Of Health Ministry No. 148 of 2010 on the Hospital licensing which not fully achieved by the hospital. 3) The violations committed by such hospitals do not have permission and had operated was not done well by local governments. In addition, local governments are not assertive in imposing sanctions in accordance with their authority. 4) Such frequently changing legislation and better coordination among related agencies do not become obstacles in the implementation of licensing hospitals in Purbalingga. 5) The efforts made to overcome the obstacles in the hospital licensing had not been implemented in an optimal, because it is only done by issuing internal regulations and socialization. The conclusion of this research is in the hospital licensing Purbalingga was not in accordance with laws and regulations.